SUBMARINE LINEATED SHEET FLOWS: A UNIQUE LAVA MORPHOLOGY FORMED ON SUBSIDING LAVA PONDS - Chadwick W.W., Jr.; Gregg T.K.P.; Embley R.W. (My University, 1999)
Lineated sheet flows are flat-lying, glassy lava flows characterized by a regular surface pattern of parallel grooves or furrows aligned with the flow direction. They are unique to the submarine environment. We propose that the lineations are developed within the collapsed interiors of partially ponded lobate sheet flows that initially inflate and then drain out during emplacement. During lava drainout, the original lobate crust founders and a new crust begins to grow on the subsiding lava surface. Lineated flow texture is created where molten lava emerges laterally from beneath a growing crust. The lineations are formed by raking of the emerging lava surface by irregularities on the bottom edge of the crust and are preserved owing to rapid chilling by seawater. Therefore, lineated sheet flows are the product of a specific sequence of events over a short period of time during the course of a deep submarine eruption.
Keywords: LINEATED SHEET FLOW; SUBMARINE LAVA MORPHOLOGY; SEA-FLOOR ERUPTIONS; MID-OCEAN-RIDGE VOLCANISM